Assessment of Biomarkers for Antioxidant Defense in the Equine Erythrocytes after Incubation with Begonia psilophylla Irmsch. Leaf Extract - Tkachenko, Halina; Buyun, Lyudmyla; Kurhaluk, Natalia; Osadowski, Zbigniew (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
In this study, the investigation of the effect of Begonia psilophylla Irmsch. leaf extract on the antioxidant defenses [catalase (CAT), glutathione reductase (GR), glutathione peroxidase (GPx) activity, ceruloplasmin level, and total antioxidant capacity (TAC)] in the equine erythrocyte suspension and plasma was undertaken. In relation to blood cells, circulating erythrocytes are regularly exposed to stress conditions and are especially vulnerable as they have no membrane repair mechanism or regenerative capacity. Freshly sampled B. psilophylla leaves were washed, weighed, crushed, and homogenized in 0.1M phosphate buffer (pH 7.4) (in ratio 1:19, w/w) at room temperature. The extract was then filtered and used for analysis. A volume of 0.1 ml of the plant extract was added to 1.9 ml of clean equine erythrocytes or 1.9 ml of plasma. For positive control, the 0.1M phosphate buffer was used. After incubation, the mixture at 37 °C for 60 min it was centrifuged at 3,000 rpm for 5 min with continuous stirring. Erythrocytes and plasma aliquots were used in the study. The presence of the extract during incubation of erythrocyte suspension and plasma caused a non-considerable increase of catalase and glutathione peroxidase activity, while the activity of glutathione reductase was not changed compared to control samples. At the same time, B. psilophylla extract caused a statistically significant decrease in ceruloplasmin level by 47.6 % (p<0.05). The total antioxidant capacity in the equine erythrocytes’ suspension and plasma after in vitro incubation with B. psilophylla leaf extract was non-significantly changed. Based on the collected data, positive trends were observed in the regressions of GPx activity against catalase activity (r=0.809, p=0.0005), and ceruloplasmin level (r=0.553, p=0.017) for in the equine erythrocytes’ suspension after in vitro incubation with B. psilophylla leaf extract. Therefore, our study suggests that crude extract obtained from B. psilophylla leaves has an effective antioxidant and anti-inflammatory effect after the treatment of equine erythrocytes. It could be interpreted that B. psilophylla extract showed the anti-inflammation effect expressed as decreasing the ceruloplasmin level in the plasma. The pronounced effect of B. psilophylla leaf extract, probably, could be attributed to its secondary metabolites content. However, the components responsible for the antioxidative activity of B. psilophylla extract is currently unclear. Therefore, further investigations need to be carried out to isolate and identify the phytochemical constituents and antioxidant compounds present in the plant extract.